Life Skills Oriented Natural Schools - trisari, nancy (Journal of Physical and Outdoor Education, 2023)
A key characteristic of positive youth development (PYD) programs is the opportunity to develop life skills, such as social, behavioral, and moral competencies, which can be generalized to domains beyond hands-on activities. The purpose of our study was to examine whether life skills-oriented nature schools have been integrated into their students. Population and sample of 29 students of Qurani Al-Hikmah Nature School. Method: quantitative descriptive with survey approach. The life skills instrument used the Life Skills Transfer Survey (LSTS), a measure of perceived life skills transfer. The results revealed that Qurani Al-Hikmah natural school oriented life skills have been integrated into the school curriculum and given daily to students bringing changes in attitudes, thoughts and behaviors by providing a pleasant school environment .